UJI TANAM VARIETAS MELON (Cucumis melo L.) DENGAN MENGGUNAKAN MULSA SINTETIK - Sartono Joko Santosa (Innofarm:Jurnal Inovasi Pertanian, 2009)
ABSTRACT The purpose of this research to test kind of synthetic mulch on melon varieties (Cucumis melo L.) begets melon fruits good quality has been done in Mranggen village, Polokarto district, Sukoharjo regency, Central of Java from 1 th December2008 until 2 th February 2009 on Regosol soil type with 150 meters above sea level. The method in this research was Split Plot Design bassed on Randomized Completely Block Design concist of two treatments and each treatment three replications. The first factor kind of varieties (main plot) concist of three kinds, there are V1 : Sweet M-10 variety, V2 : Power 70 variety, V3 : Morita 414 variety. The second factor synthetic mulch (sub plot) concist of two types, there are : M1 : white mulch plastic silver and M2 : Black mulch plastic silver. The parameters observed are height of plant, fresh weight of biomass, dry weight of biomass, time of plant in flowering, weight of fruit and circle of fruit. The result of the research are kind of synthetic mulch showed non significant effect. Kinds of varieties melon showed significant effect on circle of fruit namely Sweet M-10 variety has best circle of fruit. Key words : test of planting, melon variety, synthetic mulch, split plot design